LAND COVER SPECTRAL DATA CLASSIFICATION USING ARTIFICIAL NEURAL NETWORK (ANN) - Febri Maspiyanti; Ionia Veritawati; Amir Murtako; Riadika Mastra; Jullend Gatc (LPPM STMIK Pringsewu, 2022)
Bamboo is one of the plants in the tropics which is also a lignocellulosic natural material which can be used as a substitute for wood. There are hundreds of types of bamboo in Indonesia, where each type has its own characteristics in its use so that bamboo has potential in the industrial sector where when combined with innovation and creativity it has high economic value and is in demand by domestic and foreign consumers. The use of